The Role of Hypothalamic mTORC1 Signaling in Insulin Regulation of Food Intake, Body Weight, and Sympathetic Nerve Activity in Male Mice - Muta, Kenjiro (Endocrinology, 2015)
Insulin action in the brain particularly the hypothalamus is critically involved in the regulation of several physiological processes, including energy homeostasis and sympathetic nerve activity, but the underlying mechanisms are poorly understood. The mechanistic target of rapamycin complex 1 (mTORC1) is implicated in the control of diverse cellular functions, including sensing nutrients and energy status. Here, we examined the role of hypothalamic mTORC1 in mediating the anorectic, weight-reducing, and sympathetic effects of central insulin action. In a mouse hypothalamic cell line (GT1–7), insulin treatment increased mTORC1 activity in a time-dependent manner. In addition, intracerebroventricular (ICV) administration of insulin to mice activated mTORC1 pathway in the hypothalamic arcuate nucleus, a key site of central action of insulin. Interestingly, inhibition of hypothalamic mTORC1 with rapamycin reversed the food intake- and body weight-lowering effects of ICV insulin. Rapamycin also abolished the ability of ICV insulin to cause lumbar sympathetic nerve activation. In GT1–7 cells, we found that insulin activation of mTORC1 pathway requires phosphatidylinositol 3-kinase (PI3K). Consistent with this, genetic disruption of PI3K in mice abolished insulin stimulation of hypothalamic mTORC1 signaling as well as the lumbar sympathetic nerve activation evoked by insulin. These results demonstrate the importance of mTORC1 pathway in the hypothalamus in mediating the action of insulin to regulate energy homeostasis and sympathetic nerve traffic. Our data also highlight the key role of PI3K as a link between insulin receptor and mTORC1 signaling in the hypothalamus.